Application of morbid animal model in drug safety evaluation of traditional Chinese medicine - Ke-Yong, Ning; Min, Li (Frontiers in Pharmacology, 2015)
Further toxicology research of TCM new drugs is still necessary in animals. In some cases, it is necessary to pay more attention to the use of morbid animals in pre-clinical safety research in despite of some deficiencies.